FAKTOR RISIKO PERILAKU MASYARAKAT PADA KEJADIAN LUAR BIASA LEPTOSPIROSIS DI KABUPATEN KEBUMEN TAHUN 2017 - Diana Andriyani Pratamawati; Ristiyanto Ristiyanto; Farida Dwi Handayani; Revi Rosavika Kinansi (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2018)
Local health agency in Kebumen Regency reported that an outbreak of leptospirosis occurred in the beginning 2017. Based on the data obtained from the agency showed that a total of 60 leptospirosis cases has been successfully investigated in Kebumen Regency for January – April 2017. Among those cases, 40 patients were reported positive RDT and 6 patients were died (CFR value =10,00). The aim of this study was to determine a relationship between behavioral factors of people in Kebumen Regency with occurrence of leptospirosis and the risk factor scale of the disease. The descriptive analytic study with case control design was applied. Samples were collected using the purposive sampling method and the number of sample observed in the present study was 42 people. All data were analysed using Chi Square and Odds Ratio (OR) calculation. The results revealed that three variables of people behaviour in Kebumen Regency had positive association to occurrence of leptospirosis. They were no foot protection (barefoot) when doing activity in the yard (OR=0,25) and paddy fields (OR=0,16). Another variable was open wound without any treatment or cover (OR=0,12). It is highly recommended that staffs from local health agency should educate people for wearing sandal or other foot protections properly, particularly for those who work in the yard and paddy field. The open wound must be covered and treated in order to prevent leptospira infection.